2011
DOI: 10.1248/bpb.34.447
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interaction Study between Bupropion and Ticlopidine in Male CF-1 Mice

Abstract: Bupropion is an atypical antidepressant that is biotransformed in humans to its major active metabolite hydroxybupropion by cytochrome P450 2B6 (CYP2B6). Co-administration of bupropion with an inhibitor of CYP2B6 can result in a serious drug interaction, leading to bupropion related adverse effects (e.g. seizures). The antiplatelet agent ticlopidine has been identified as a potent in vitro inhibitor of bupropion hydroxylation, however it is unknown if it interacts in vivo in rodents. In this study we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…4). Bupropion hydroxylation, a marker of Cyp2b (Molnari et al, 2011), was increased (40-fold) in the absence of the three Cyp gene clusters, which could be accounted for by the induction of Cyp2b10 protein (Fig. 2C).…”
Section: Resultsmentioning
confidence: 95%
“…4). Bupropion hydroxylation, a marker of Cyp2b (Molnari et al, 2011), was increased (40-fold) in the absence of the three Cyp gene clusters, which could be accounted for by the induction of Cyp2b10 protein (Fig. 2C).…”
Section: Resultsmentioning
confidence: 95%
“…Recently, our laboratory confirmed these in vitro and in vivo findings by demonstrating that ticlopidine significantly inhibits bupropion metabolism in mice (Molnari et al 2011). We showed that CF-1 mice pretreated with ticlopidine exhibited a statistically significant increase in the area under the concentration time curve (AUC) of bupropion in both plasma and brain tissues, whereas the AUC of bupropion's metabolite hydroxybupropion was reduced (Molnari et al 2011).…”
Section: Introductionmentioning
confidence: 69%
“…Mice were chosen as a representative animal species for this project since: (a) in comparison to rats, the conversion of bupropion to its major active metabolite hydroxybupropion in mice is more closely related to humans (Suckow et al 1986); (b) others have successfully used CF-1 mice to study drug interactions between bupropion and other psychotropic agents (Wang et al 2006); and (c) our previous studies used CF-1 mice to demonstrate a PK drug-drug interaction between bupropion and prototypical CYP2B6 inhibitor ticlopidine (Molnari et al 2011). Male CF-1 mice (30-35 g) aged 3 months were obtained from Charles River Laboratories (Wilmington, MA) and individually housed in the Drake University Animal Care facility under 12 h light-dark cycles with free access to food and water.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations